SECURE AND RECOVERABLE SPLIT KEY MANAGEMENT TECHNIQUE FOR CLOUD STORAGE - S, Theophilus Rakesh; Kv, Pradeep (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Establishing mutual trust between a cloud service provider (CSP) and a client has always been a challenge. Managing the key as a whole on either of these sites poses a security risk and also questions the integrity and availability of the data itself. In this paper, we propose an effective solution to manage key at the client's location, while the CSP still manages a portion of the key. The proposed technique secures the key itself and also provides a fail-safe mechanism to retrieve the key if lost.